2012
DOI: 10.4028/www.scientific.net/amr.626.298
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of TiAlBN Nanocomposite Coating Deposited via Radio Frequency Magnetron Sputtering Using Single Hot-Pressed Target

Abstract: Abstract. TiAlBN coatings have been deposited at varying bias voltage of 0, -60, and -150 V by radio frequency (RF) magnetron sputtering technique. A single hot-pressed Ti-Al-BN target was used for the deposition process. With glancing angle X-ray diffraction analysis (GAXRD), the nanocrystalline (nc-) (Ti,Al)N phase was identified. In addition, the existence of BN and TiB 2 amorphous (a-) phase were detected by X-ray photoelectron spectroscopy (XPS) analysis. Thus, the deposited TiAlBN coatings were confirmed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
5
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 13 publications
0
5
0
Order By: Relevance
“…All of the deposited coatings showed diffraction peaks corresponding to TiN phase at plane (111), (200), and (220). The TiB 2 and BN phases were not detected in the GAXRD spectra as these phases exist as an amorphous [10]. It can be seen that the intensity of the TiN peaks of plane (111) and plane (200) were affected when the R N was varied.…”
Section: Resultsmentioning
confidence: 99%
“…All of the deposited coatings showed diffraction peaks corresponding to TiN phase at plane (111), (200), and (220). The TiB 2 and BN phases were not detected in the GAXRD spectra as these phases exist as an amorphous [10]. It can be seen that the intensity of the TiN peaks of plane (111) and plane (200) were affected when the R N was varied.…”
Section: Resultsmentioning
confidence: 99%
“…Similarly, the N 1s peak can be curve fitted into two main components corresponding to (Ti,Al)N (397 eV for sample deposited at 15% R N , and 396 eV and 397 eV for sample deposited at 5% R N ) and BN (398 eV). Since BN and TiB 2 phase was not detected by GAXRD, (published elsewhere in [14,15]), thus, it can be deduced that they exist in amorphous phase. In addition, it was found that the amount of BN and TiB 2 phase differs with varying R N (indicated from the intensity of BN and TiB 2 peaks).…”
Section: Resultsmentioning
confidence: 99%
“…Deposition of TiAlBN nanocomposite coatings were conducted using PSP5004 SNTEK radio frequency (RF) magnetron sputtering. Detail of the deposition parameters can be found elsewhere [14,15]. The TiAlBN nanocomposite coatings were deposited at various nitrogen- to-total gas flow ratio (R N ) of 5, 15, 20, and 25%, and at various substrate temperature of 100, 200, 300, and 400ºC.…”
mentioning
confidence: 99%
“…Recently, a nanocomposite TiAlBN coating was successfully deposited via r.f. magnetron sputtering technique on a steel substrate which consist of nc-(Ti,Al)N, a-BN and a-TiB 2 phases [10][11]. Nitride based hard coatings like TiN, (TiAl)N, BN and etc.…”
Section: Introductionmentioning
confidence: 99%